2021
DOI: 10.1111/sjos.12509
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Bayesian inference for a spatial point process model exhibiting regularity and random aggregation

Abstract: In this article, we propose a doubly stochastic spatial point process model with both aggregation and repulsion. This model combines the ideas behind Strauss processes and log Gaussian Cox processes. The likelihood for this model is not expressible in closed form but it is easy to simulate realizations under the model. We therefore explain how to use approximate Bayesian computation (ABC) to carry out statistical inference for this model. We suggest a method for model validation based on posterior predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, in order to supply a shared process specification under geostatistical modeling, employing GPs is most convenient. In this regard, recent work (Virhs et al, 2021) introduces spatial aggregation to a Gibbs process using a GP and offers the possibility of further PS investigation. Another path for future work involves spatio-temporal response data collection, opening the potential of spatial bias varying over time in the data collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to supply a shared process specification under geostatistical modeling, employing GPs is most convenient. In this regard, recent work (Virhs et al, 2021) introduces spatial aggregation to a Gibbs process using a GP and offers the possibility of further PS investigation. Another path for future work involves spatio-temporal response data collection, opening the potential of spatial bias varying over time in the data collection.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, I consider three classes of parametric spatial point process models as examples: log-Gaussian Cox processes (LGCP) , Strauss processes (Strauss, 1975, Kelly and, and LGCP-Strauss processes (Vihrs et al, 2022). I briefly define these in the following subsections and refer to the above references for more details about these models.…”
Section: Simulation Study For Examples Of Point Process Modelsmentioning
confidence: 99%
“…There is a tendency for overestimating σ 2 unless the true value is above circa 3 in which case it is usually underestimated. Vihrs et al (2022) also found it to be difficult to make inference about the parameters of the Gaussian random field in an LGCP-Strauss process and related it to the fact that it can be difficult to see the effect of changes in the Gaussian random field from a realization of the process because it is obscured by the small scale regularity.…”
Section: Lgcp-strauss Processesmentioning
confidence: 99%
See 2 more Smart Citations